Covid-19 and agricultural labor supply: Evidence from the rural–urban interface of an Indian mega-city - Verena Preusse; Manuel Santos Silva; Linda Steinhübel; Meike Wollni (Agribusiness, 2024)
This paper examines how India's national lockdown (March 25–May 31, 2020), in response to the spread of Covid-19, affected the on-farm family labor supply of 351 farm households in the rural–urban interface of Bangalore. We combine face-to-face survey data collected just before the start of the lockdown with phone survey data collected during the last 20.167emweeks of the lockdown. We find that 66% of farm households reduced their daily on-farm family labor supply during the lockdown, by on average almost 40% compared with prelockdown levels. Changes in on-farm family labor supply differed by key pre-Covid-19 household characteristics. Farm households that were engaged in crop marketing decreased their on-farm family labor supply by an average of 3–40.167emh/day. In turn, farm households that relied on off-farm income increased their on-farm family labor supply by on average 3–40.167emh/day
Keywords: 630; agricultural households; agricultural markets; Covid-19; India; lockdowns; on-farm labor supply